Tanggung Jawab Keluarga Sebagai Pusat Pendidikan Rohani: Analisis Ulangan 6:4-9 - Andri Harvijanto (JURNAL ILUMINASI, 2024)
The book of Deuteronomy is the story of the history of the Israelites as God's chosen people, who live their lives only because of God's leadership and power. Living by loving God with all your heart, strength and mind is the only way to experience God's power and love. The book's actual name in Hebrew is summarized in the opening line that reads "these are the words". The book of Deuteronomy is addressed to the Israelites as a people who have been bound by a Covenant with God. The messages given by Moses were intended for the Israelites in an effort to prepare the Israelites before entering the land of Canaan. Therefore Deuteronomy 6:4-25 is a summary of the maturing process of family faith in Israel called Shema which must receive full attention and recognition for families in God. The confession of faith is an acknowledgment that states the oneness and uniqueness of the Lord God of Israel, specifically in God's relationship with His people, and how God's people should respond to God.